Combined IL-2, agonistic CD3 and 4-1BB stimulation preserve clonotype hierarchy in propagated non-small cell lung cancer tumor-infiltrating lymphocytes. Issue 2 (2nd February 2022) - Shah, Parin; Forget, Marie-Andrée; Frank, Meredith L; Jiang, Peixin; Sakellariou-Thompson, Donastas; Federico, Lorenzo; Khairullah, Roohussaba; Neutzler, Chantal Alexia; Wistuba, Ignacio; Chow, Chi-Wan B; Long, Yan; Fujimoto, Junya; et al.
Abstract : Background: Adoptive cell transfer (ACT) of tumor-infiltrating lymphocytes (TIL) yielded clinical benefit in patients with checkpoint blockade immunotherapy-refractory non-small cell lung cancer (NSCLC) prompting a renewed interest in TIL-ACT. This preclinical study explores the feasibility of producing a NSCLC TIL product with sufficient numbers and enhanced attributes using an improved culture method. Methods: TIL from resected NSCLC tumors were initially cultured using (1) the traditional method using interleukin (IL)-2 alone in 24-well plates (TIL 1.0) or (2) IL-2 in combination with agonistic antibodies against CD3 and 4-1BB (Urelumab) in a G-Rex flask (TIL 3.0). TIL subsequently underwent a rapid expansion protocol (REP) with anti-CD3. Before and after the REP, expanded TIL were phenotyped and the complementarity-determining region 3 β variable region of the T-cell receptor (TCR) was sequenced to assess the T-cell repertoire. Results: TIL 3.0 robustly expanded NSCLC TIL while enriching for CD8 + TIL in a shorter manufacturing time when compared with the traditional TIL 1.0 method, achieving a higher success rate and producing 5.3-fold more TIL per successful expansion. The higher proliferative capacity and CD8 content of TIL 3.0 was also observed after the REP. Both steps of expansion did not terminally differentiate/exhaust the TIL but a lesser differentiated population was observed after the first step. TIL initially expanded with the 3.0 method exhibited higher breadth of clonotypes than TIL 1.0 corresponding to a higher repertoire homology with the original tumor, including a higher proportion of the top 10 most prevalent clones from the tumor. TIL 3.0 also retained a higher proportion of putative tumor-specific TCR when compared with TIL 1.0. Numerical expansion of TIL in a REP was found to perturb the clonal hierarchy and lessen the proportion of putative tumor-specific TIL from the TIL 3.0 process. Conclusions: We report the feasibility of robustly expanding a T-cell repertoire recapitulating the clonal hierarchy of the T cells in the NSCLC tumor, including a large number of putative tumor-specific TIL clones, using the TIL 3.0 methodology. If scaled up and employed as a sole expansion platform, the robustness and speed of TIL 3.0 may facilitate the testing of TIL-ACT approaches in NSCLC.